If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-3/8)*z = 9
27/(-9) = 0
y = (3/8)*x^2+3*x+2;3/8;3;2
-((3^2-(2*4*(3/8)))/(4*(3/8)))
-(3/(2*(3/8)))
| -3/8z=9 | | x^2+kx+21=0 | | 3x-4+2x=26 | | -7x+13=-5x+9 | | 3=4x^2+3x-7 | | -3x+13=4 | | -3x-4=-4x-10 | | 2=5(x+9)+8x | | 5x-6=-x-30 | | (4z^6-2z^3+5)(z^3+27i)=0 | | -2x+18=-4x+34 | | 27/(-9) | | -9x+22+11x+21=2 | | 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 | | -6=-2/3y | | 3x+18=-3x-6 | | 6n+11-8n=22 | | X^3-1/X^3=14 | | 7=8(x+5)+5 | | 3.4a=7.004 | | 1=1/3x^2 | | 5(11-3x)+4(2x+1)=3 | | 7(x+4)-(3x-1)=8 | | (3x+4)=5x | | y=ctg(1-2x) | | y=ctg(1-2xz) | | 2+2+3=3 | | (12x+20)+(7x)+(20x-35)=180 | | 6=6(x+5)-2x | | (3x+7)=(5x-3) |